1977
DOI: 10.1063/1.89426
|View full text |Cite
|
Sign up to set email alerts
|

Coherent anti-Stokes Raman scattering in a hollow dielectric waveguide

Abstract: Hollow waveguides are shown to enhance coherent anti-Stokes Raman scattering by two to three orders of magnitude for low-pressure gases. Theoretical and experimental comparisons of signals generated by tight focusing in a cell with those generated in a hollow waveguide are preented. These arguments show that maximum conversion in the hollow waveguide occurs at pressures on the order of several atmospheres compared to greater than 50 atm for tight focusing, and for low pressures enhancements are on the order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 10 publications
1
21
0
1
Order By: Relevance
“…High-order, nongrazing modes have high loss and thus are of limited use for enhancement of nonlinear interactions. Most classic hollow-capillary, nonlinear optics enhancement experiments that have been reported describe output signals that required phase matching and consequently did not benefit from the collection of a large number of waveguide modes or the collection of a large solid-angular output [5][6][7][8][9]11,12]. Thus these experiments are not strongly affected by the requirement of grazing incidence.…”
Section: B Related Work Capillary Tubesmentioning
confidence: 80%
See 1 more Smart Citation
“…High-order, nongrazing modes have high loss and thus are of limited use for enhancement of nonlinear interactions. Most classic hollow-capillary, nonlinear optics enhancement experiments that have been reported describe output signals that required phase matching and consequently did not benefit from the collection of a large number of waveguide modes or the collection of a large solid-angular output [5][6][7][8][9]11,12]. Thus these experiments are not strongly affected by the requirement of grazing incidence.…”
Section: B Related Work Capillary Tubesmentioning
confidence: 80%
“…It is noted that classical hollow capillary tubes have also been used for the enhancement of nonlinear optical interactions [5][6][7][8][9][10][11][12][13]. These capillaries work best with rays that propagate at grazing incidence, i.e., when only the fundamental EH 11 or low-order waveguide mode propagates [14][15][16][17][18].…”
Section: B Related Work Capillary Tubesmentioning
confidence: 99%
“…The fibre also can be bent so that the entire device can be made compact. Using an enhancement factor λl/a 2 [92], where l is the constant intensity interaction length and a is the beam radius, it has been demonstrated that the low loss HC-PCFs can beat capillary guides by the factor ∼ 10 6 [13]. This remarkable efficiency boost is due to the fact that in hollow capillary waveguides l is limited by loss and scales as l ∼ a 3 /λ 2 [93], while in high quality PCFs l practically equals the fibre length.…”
Section: Nonlinear and Quantum Optics In Hollow-core Pcfsmentioning
confidence: 99%
“…25,26 Similarly to gas-filled hollow fibers, the waveguide regime of non-linear optical interactions in our structure improves the efficiency of wave-mixing and harmonic-generation processes relative to the regime of tightly focused pump beams owing to a radical increase in the interaction length. On the other hand, a periodic perturbation of the refractive index introduced by the diffraction grating (see the inset in Fig.…”
Section: The Waveguide Structure and The General Ideamentioning
confidence: 99%